Finite nonabelian p-groups having exactly one maximal subgroup with a noncyclic center - Janko, Zvonimir (Archiv der Mathematik, 2011)
We prove here that a nonabelian finite p-group G has exactly one maximal subgroup with a noncyclic center if and only if Z(G) is cyclic and G has exactly one normal abelian subgroup of type (p, p).
Gesehen am 04.07.2022